Easing of America’s Healthcare Burden: The Case for Aggressive Prevention of the Metabolic Syndrome - Lane, Gerry (Journal of Nutritional Therapeutics, 2016)
The term “metabolic syndrome” was used in 1977 by Herman Haller who was studying the risk factors associated with atherosclerosis. In the same year, Dr. Singer used the term to describe the associations between hyperlipoprotenemia and obesity, gout, diabetes mellitus, and hypertension. In1988, Gerald Reaven hypothesized that insulin resistance could be the underlying factor linking this constellation of abnormalities, which he went on to name “syndrome X or Reaven’s syndrome”. Regardless of the clinical term that is utilized, the global impact on health care resources and humanity is massive. 47 million adult patients meeting the criteria for metabolic syndrome which represent over 24% of the adults in the United National inpatient hospital costs for metabolic syndrome with complications were nearly 400 billion in With appropriate primary care for the complications of metabolic syndrome, nearly 17 billion in hospital costs might have been averted, with significant potential savings obtained in US government health care programs. Non-pharmacological approaches to fight the risk factors associated with metabolic syndrome have been known for The scientific evidence supports the efficacy of nutritional Metabolic syndrome is a preventable life threatening disease process. With its roots in childhood, this vicious cycle slowly destroys lives while we spend billions in the process. Delegating responsibility of financing our health and wellness to the insurance industry, Americans are ill prepared to deal with the reality that health is neither a luxury nor an entitlement. The impact of accepting the responsibility of prevention through nutritional counseling and education combined with regular exercise could save billions of dollars annually. More importantly aggressively preventing metabolic syndrome would save millions of lives.